2022
DOI: 10.21203/rs.3.rs-2361702/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monkeypox and cancer: a pan-cancer based multi-omics analysis and single cell sequencing analysis

Abstract: Background: Monkeypox is a zoonotic disease caused by monkeypox virus, and most infections cause systemic disease. Tumor patients are susceptible to various viruses, but there are few reports on the effects of genes related to monkeypox virus infection on the tumor microenvironment. Therefore, we need to further explore the expression of genes associated with monkeypox infection in tumor patients and the potential immune mechanisms in order to improve the survival and prognosis of tumor patients. Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Mpox infection was linked with abnormal Mpox-related genes (MpoxRGs) expression, which significantly correlated with tumor immunology and the drug response pathway when activated [ 56 ]. This MpoxRGs was found to be expressed differently in varieties of tumor cells and was also used as prognostic markers in tumors [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mpox infection was linked with abnormal Mpox-related genes (MpoxRGs) expression, which significantly correlated with tumor immunology and the drug response pathway when activated [ 56 ]. This MpoxRGs was found to be expressed differently in varieties of tumor cells and was also used as prognostic markers in tumors [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mpox might be capable of influencing carcinogenesis, according to a survival analysis that revealed that a high MpoxRG score was often strongly related to a bad tumor prognosis [ 57 ]. Similarly, a genetic study showed that MpoxRG copy quantity and single nucleotide variants were related to tumor longevity [ 56 ]. MpoxRG alterations were significantly correlated with survival, indicating that tumor prognostic may be impacted by polymorphisms [ 57 ].…”
Section: Discussionmentioning
confidence: 99%